Burden of Musculoskeletal Disorders, Associated Risk Factors and Perceptions on Prevention Among Airport Baggage Handlers - Trivedi, Ashish A, MD; Lai, Alice; Tasim, Mahmud; Tuah, Nik (UI Scholars Hub, 2025)
Background Airport baggage handlers are involved in manual handling of heavy loads, predisposing them to the risk of developing work-related musculoskeletal disorders (MSDs). This study aimed to determine the burden of self-reported MSDs and their associated factors among airport baggage handlers in Brunei Darussalam. Methods In this cross-sectional study, we used a self-administered questionnaire to collect demographic and work profile data. We also incorporated the Nordic Musculoskeletal Questionnaire to assess body-part MSD symptoms over a 12-month period. Baggage handlers’ perceptions of the likelihood of specific work tasks related to MSDs and of preventative measures were also sought. The data were summarized using descriptive statistics, and Pearson’s chi-square test and multiple logistic regression were used to assess the statistical significance of associations between demographic and work factors and MSD burden. Results The study received a response rate of 58%. 12-month proportion for self-reported MSD was 86.5%. Low back pain (70%), upper back pain (62%), and shoulder pain (43%) were commonly reported MSDs. Loading containers in the baggage room, baggage handling inside narrow-body aircraft, and pushing/pulling trailers were found to be high-risk work tasks for MSD symptoms. Improved staff rostering, reduced process pace, and the use of ‘heavy’ tags were perceived as beneficial control measures. Conclusion The 12-month proportion of self-reported MSDs was high (86.5%) among airline baggage handlers. Longer employment duration and baggage handling in narrow-body aircraft were significantly associated with higher MSDs. These findings indicate the need to reinforce workplace policies, procedures, resource allocation, and targeted interventions to prevent MSD in this occupational group.